SYNTACTIC ANALYSIS OF THE STRUCTURE OF MEDICAL TERMINOLOGY IN THE ENGLISH AND UZBEK LANGUAGES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The most effective units within the medical terminology system are considered in the field of English medical terminology. The formation of terms, especially the structure of terminological units, is considered the most important aspect in the process of filling in learned terminology. This article discusses the morphological and syntactic analysis of forming English and Uzbek medical terms that have been studied and researched.